Design of Experimental Series on the Free Fall of Object: https://doi.org/10.69692/SUJMRD0802236 - VONGVIZAY, Pathom; VONGTONGKHAM, Bounchan; MINGKEO, Manivan (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
An experimental set for measuring the gravitational acceleration to compare free falling motion was developed in this research. It used DIY relay by a simple relay control to o’clock automatically measure to free falling time of the object. The measured falling time was displayed on a general clock which the user could read it. Recorded falling time at different falling height was analyzed to get the gravitational acceleration. The results showed that the value of measured gravitational acceleration was very close to the standard value. The magnitude of the gravitational pull measured from the developed machine is equal to And can be measured from a company machine Compare with the gravitational field value of the standard measured by the National Institutes of Health, Bangkok, Thailand, which is equal to . It’s percentage of deviation from standard value was 0.918% and, it’s percentage of deviation from Ready-made gantry fall testing machine value was 0.481%. This experimental set demonstrates that it can be used to measure the gravitational acceleration effectively.